Pelanggaran Etika Atas Pemalakan dan Bullying di Universitas Diponogoro - Zahwa Putri Sabila; Putri Juliana; Sifani Jannah; Mohammad Zein Saleh (Journal of Management and Creative Business, 2025)
Business ethics in an academic environment, especially in universities such as Diponegoro University, plays a crucial role in shaping campus culture. However, the rampant cases of extortion and bullying among Undip PPDS students have disturbed the ethical values that should be upheld. Such actions are not only psychologically harmful, but also damage academic integrity and professionalism. This study aims to understand and analyze the root causes of ethical violations in the context of medical education, as well as their impact on individuals, the academic community, and institutional reputation. Thus, it is expected to contribute to efforts to prevent and handle similar cases in the future.